PERBEDAAN PENGUASAAN KOSAKATA ANAK USIA 5-6 TAHUN MELALUI PERMAINAN TRADISIONAL ABC LIMA DASAR DI TK ABA 01 MEDAN TA. 2024/2025 - Tiara Alpina Damanik; Wan Nova Listia (CV. ADIBA AISHA AMIRA, 2025)
The purpose of this study was to determine whether there was a difference in vocabulary mastery of children age 5-6 years through traditional ABC five basic games in ABA 01 Kindergarten Medan. This type of research uses a quantitative approach with an experimental method in the from of One Group Pretest-Posttest Design. The sample in this study was class B Khadijah with 14 children. The tool used for data collection was an observation sheet. Before conducting hypothesis analysi using the paired sample T-test, a normality test was first conducted using the Shapiro Wilk statistical test. From the results of the hypothesis test analysis of the pretest and posttest data on children’s vocabulary mastery, the data results were 0.000. So it can be stated that there is a significant difference between the pretest and posttest data on the vocabulary mastery of children aged 5-6 years through the five basic ABC games at ABA 01 Medan Kindergarten.